Detection and analysis of the modes of variability between surface currents and chlorophyll a in the Tropical Atlantic - OLIVEIRA, Isabelle Maria Vilela de (2019)
The main objective of this study is to estimate and analyze the relationship of surface circulation variability with the spatial and temporal distribution of Chlorophyll a (Chl) in the Tropical Atlantic Ocean (TA). (1) Quantification of the main spatial and temporal variability patterns of surface currents and Chl in the TA, (2) estimative of the coupled modes of variability between surface circulation and Chl in TA. A dataset of 15-year Aqua-MODIS (Moderate Resolution Imaging Spectroradiometer) sensor data was used to determine Chl variability in the TA. In addition, 24 years of monthly surface currents data were used to investigate the main modes of variability of the surface circulation of the TA based on satellite data. The statistical method of Empirical Orthogonal Function (EOF) was applied in order to analyze the modes of Chl and surface currents variability. This study identifies the main spatial and temporal patterns of surface circulation, Chl, and the connection of Chl anomalies with the circulation of the TA through coupled modes. The EOF1 between currents and Chl (~ 25%) shows a strong covariance in the region of the equatorial divergence and the Amazon plume dispersion. The EOF2 (~ 9%) shows high covariance in the Amazon plume and, in the south, the positive anomalies are restricted to the region of influence of the Congo River. The EOF3 (~ 6%) shows an increase in the patterns of zonal current anomalies south of the equator, and at the coast of Africa, associated with a substantial increase in Chl in most of the basin. These results support future studies on large scale climate variability, thermohaline circulation, oceanic fluxes, CO2 absorption and ecological impacts in the food chain over the TA.